Genetic polymorphisms and population genetic analyses of 57 autosomal InDel loci in Hubei Tujia group - Lan, Jiangwei; Zhang, Xingru; Cui, Wei; Mei, Shuyan; Xu, Jingtao; Zhu, Bofeng (Frontiers in Genetics, 2023)
Introduction: The Tujia is the eighth most populous population in China, but its genetic structure has not been fully studied. Methods: In this study, we utilized 57 autosomal Insertion/deletion (InDel) loci to evaluate the genetic polymorphisms and efficiency of forensic applications in the Chinese Hubei Tujia group, and analyzed the genetic structure variances among the studied group and other 26 different reference populations from five continents in 1000 Genomes Project (1KG). Results: The results showed that 57 InDels have no significant deviations from Hardy–Weinberg equilibrium and linkage equilibrium. The combined power of discrimination (CPD) and the combined probability of exclusion (CPE) values for 57 InDels were 0.99999999999999999999999699822 and 0.999975177214539 in the Hubei Tujia group, respectively. In addition, the results of genetic structure analyses indicated that the Hubei Tujia group has close genetic relationships with the Chinese Han population and other East Asian populations. Discussion: These 57 autosomal InDels can be used as reliable tools for forensic individual identification and paternity testing, and are more suitable for East Asian populations. Furthermore, three InDels (rs72085595, rs145941537, and rs34529639) are promising for inferring ancestral information.